Paleo-Geohydrology of Lake Chilwa, Malawi is the Source of Localised Groundwater Salinity and Rural Water Supply Challenges - Michael O. Rivett; Shona Symon; Lucas Jacobs; Limbikani C. Banda; Gift J. Wanangwa; Donald J. C. Robertson; Ibrahim Hassan; Alexandra V. M. Miller; Geoffrey M. S. Chavula; Chrispine E. Songola; Chikondi Mbemba; Marc J. Addison; et al. (Applied Sciences, 2020)
Meeting long-term rural community water supply needs requires diligent geohydrological conceptualisation. Study of Malawi’s Lake Chilwa Basin, including sampling of 330 water points in Phalombe District, enabled assessment of groundwater quality influence upon supply. The control of larger Lake Chilwa paleo-environments on current Basin groundwater quality is demonstrated. Lacustrine sediment deposition forming high-level deposits under open lake conditions and terrace deposits under open and closed lake conditions significantly control the groundwater major-ion quality and salinity now observed. Paleo-lake extent marks the transition between low-TDS (total dissolved solids) groundwater suitable for water supply at higher elevations and high-TDS brackish groundwater in areas overlain by lacustrine deposits closer to the current lake level. Low-TDS groundwater is limited to mid-to-low reach influent leakage of rivers incising terraces. Permeable fluvial deposits within the deeper paleo-river channel may possibly provide low-TDS water. The conceptual model, whereby paleo-lake controls groundwater salinity, provides science-based evidence to address policy to manage the significant water point functionality concerns quantified at the district and river basin scales. Targeting of the low-TDS groundwater alongside improved use of upland low-TDS stream/river sources with fewer, but larger capacity, and better maintained gravity-fed supply schemes are recommended. This study hence shows the value of paleo-geohydrology interpretation of the lake–groundwater system conceptualisation to inform Sustainable Development Goal 6 (SDG 6.5.1)—integrated water resources management policy for rural water supply.